2020
DOI: 10.1177/2374373519892416
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Perception of Cell Phone Usage in a Teaching Hospital Setting

Abstract: Objective: To evaluate perceptions regarding cell phone use in a teaching hospital setting among health care providers, residents, medical students, and patients. Methods: Fifty-three medical students, 41 resident physicians, 32 attending physicians, and 46 nurses working at University Hospital completed a questionnaire about cell phone use practices and their perceptions of cell phone use in the hospital. Forty-three inpatients admitted to medical/surgical units at University Hospital were surveyed at bedside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A cross-sectional, survey-based study conducted among the health professionalsestimatedthat87%ofhealthcarepr ofessionalsusingsmartphoneortabletattheirwor kplace. 5 The health professionals reported that smartphone use assisted quickly in resolving the personal issues and reducing thestress. 6 A study conducted regarding the effects of mobile phone use in clinical practice reported that accessing mobile phone during clinical practice does not only interfere the patient care but also it facilitates the effective and continuous patientcare, fastest access to the healthcare information and increases the knowledge as well as improves the care givingskills.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional, survey-based study conducted among the health professionalsestimatedthat87%ofhealthcarepr ofessionalsusingsmartphoneortabletattheirwor kplace. 5 The health professionals reported that smartphone use assisted quickly in resolving the personal issues and reducing thestress. 6 A study conducted regarding the effects of mobile phone use in clinical practice reported that accessing mobile phone during clinical practice does not only interfere the patient care but also it facilitates the effective and continuous patientcare, fastest access to the healthcare information and increases the knowledge as well as improves the care givingskills.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional, survey-based study conducted among the health professionalsestimatedthat87%ofhealthcarepr ofessionalsusingsmartphoneortabletattheirwor kplace. 5 The health professionals reported that smartphone use assisted quickly in resolving the personal issues and reducing thestress. 6 A study conducted regarding the effects of mobile phone use in clinical practice reported that accessing mobile phone during clinical practice does not only interfere the patient care but also it facilitates the effective and continuous patientcare, fastest access to the healthcare information and increases the knowledge as well as improves the care givingskills.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a wealth of literature on the use of mobile technology in medical education, most literature focuses on the impact and perceptions of medical students, residents, and teachers [ 1 , 5 , 6 ]. The two papers which involved perceptions of patients are either focused on healthcare workers or on patient confidentiality in using mobile devices [ 14 , 15 ]. Patients’ perceptions of using mobile devices in teaching and learning context are often neglected.…”
Section: Introductionmentioning
confidence: 99%